Kidney anomalies diagnosed by prenatal ultrasound screening and associated non‐urinary malformations: a nationwide prevalence study. (28th July 2016) - Rasmussen, Maria; Olsen, Morten Smærup; Sunde, Lone; Sperling, Lene Søndergård; Petersen, Olav Bjørn
Abstract: Objectives: To estimate the prevalence of kidney anomalies at second trimester ultrasound screening, and furthermore, to investigate pregnancy outcomes and the pattern of additional malformations. Methods: We previously identified all women attending second‐trimester ultrasound scans in Denmark between 1 January 2007 and 31 December 2012. Using the Astraia databases and the Danish National Patient Registry, we identified all fetuses with kidney anomalies diagnosed prenatally in these women. In addition to the prevalence of fetuses with kidney anomalies, we estimated the live birth prevalence ratio of non‐urinary malformations, comparing the prevalences in infants with and without prenatally diagnosed kidney anomalies. Results: The prevalence of fetuses with kidney anomalies at second trimester scans was 11.4 per 10 000 fetuses. Among the 412 fetuses identified, 127 pregnancies were terminated. For live born children the prevalence of additional non‐urinary malformations was four times higher (95% CI: 3–5) compared with the prevalence among children without prenatal kidney anomalies. Digestive system anomalies were particularly prevalent. Conclusion: These population‐based data provide additional insight into the course of pregnancy and birth outcomes following prenatal diagnoses of kidney anomalies. © 2016 John Wiley & Sons, Ltd. Abstract : What's Already Known About This Topic? Previous studies on prevalence have mixed prenatally and postnatally detected cases. Previous studies have indicated an increased risk of additional non‐urinary malformations but they have not included a comparison population. What Does This Study Add? Based on nationwide data we estimate a prevalence of prenatally detected kidney anomalies. Our data indicate that syndromes, especially those including defects in the digestive system, should be considered when prenatal kidney anomalies are detected.